All aboard for the Bobo Road - Davies, Stephen, 1976-; Corr, Christopher (Minneapolis : Andersen Press USA, 2017)
"In Burkina Faso, Fatima and Galo load the luggage while their dad Big Ali drives the bus. Help count bikes, sacks of rice, melons and even goats and chickens as the bus travels past Gurunsi houses, the hippo lake, waterfalls and jungle, all the way to Bobo"--
"First published in 2015 by Andersen Press Ltd, London"--Copyright page.
Keywords: Buses -- Fiction; Counting; Burkina Faso -- Fiction